2010
DOI: 10.3109/02813432.2010.505412
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cancer alarm symptoms: A population-based cross-sectional study

Abstract: Objective . To estimate the prevalence of alarm symptoms for breast, colorectal, urinary tract, and lung cancer in the general population. Design. Cross-sectional questionnaire survey. Setting. The former County of Funen, Denmark, with 480 000 inhabitants. Participants . A total of 13 777 randomly selected persons aged 20 years and older. Main outcome measures . Prevalence estimates of having experienced cancer alarm symptoms during the past 12 months: a lump in the breast, blood in bowel movements, blood in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 16 publications
1
27
2
1
Order By: Relevance
“…21 This is confirmed by the findings of Ingebrigtsen et al and Scheel et al, who found that warning signs of cancer were present in 12.4% 8 of all GP consultations and that suspicion was raised in only 24% 9 of these consultations. However, these figures cannot be compared with the 5.7% found in this study as the authors of the former studies only asked for information on suspicion if a warning sign was present, whereas this study inquired whether there was a suspicion of cancer or another serious disease for all patients seen.…”
Section: Provenancesupporting
confidence: 77%
“…21 This is confirmed by the findings of Ingebrigtsen et al and Scheel et al, who found that warning signs of cancer were present in 12.4% 8 of all GP consultations and that suspicion was raised in only 24% 9 of these consultations. However, these figures cannot be compared with the 5.7% found in this study as the authors of the former studies only asked for information on suspicion if a warning sign was present, whereas this study inquired whether there was a suspicion of cancer or another serious disease for all patients seen.…”
Section: Provenancesupporting
confidence: 77%
“…In questionnaire studies of the general population, 14–33% report that they have experienced rectal bleeding at some time in their life, and rectal bleeding in the last year is reported by 6–19% depending on the age of the responders [27], [28]. In the general population, the positive predictive value of rectal bleeding is estimated to be 0.1%, but once the symptom has been reported to the GP, the positive predictive value rises to approximately 3% [28].…”
Section: Discussionmentioning
confidence: 99%
“…4 However, as these symptoms are non-specific and common in the general population, most patients who are investigated will not have the disease. 5,6 This places a considerable burden on diagnostic services and highlights the need for diagnostic tests that are not only sensitive and specific, but widely available, safe and acceptable to patients.…”
Section: Introductionmentioning
confidence: 99%